Peningkatan Visibilitas dan Keselamatan Pengguna Jalan melalui Pemasangan Reflektor Jalan dan Penerangan Jalan Umum Berbasis Sensor Photocell di Desa Kemejing - Sefiyuchanna Sefiyuchanna; Nur Baiti Jannati; Tyastiana Tyastiana; Dina Lutfa Azizi; Gian Adfad; Intan Ramadhany; Khofifah Nur Hasanah; Krisna Dwi Hartanto; Muhammad Miftakhus Salam; Muhammad Rafi Firnanda; Ni'matul Holisoh; Rifig Al Wafaa; Riza Maysharoh; Sylvia Wulandari; Tiya Feza Qarina; Yuangga Ilham Akbar (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Kemejing Village is geographically hilly with winding roads and minimal lighting, reducing visibility and potentially compromising the safety and security of road users, especially at night. This community service activity aims to improve visibility and safety for road users in Kemejing Village, Loano District, Purworejo Regency, by installing road reflectors and street lighting (PJU) using photocell sensors. The method used was community empowerment based on field actions, which included observation, planning, implementation, and evaluation, involving students, village officials, and the community. The results of this activity showed that the road reflectors and PJU using photocell sensors successfully improved visibility at night, provided automatic and energy-efficient lighting, and made road users feel safer and more comfortable. This activity provided positive benefits to the community and helped build village infrastructure that can continue to develop in line with the Sustainable Development Goals (SDGs).